Prenatal binge-like alcohol exposure alters brain and systemic responses to reach sodium and water balance. (17th December 2015) - Godino, A.; Abate, P.; Amigone, J.L.; Vivas, L.; Molina, J.C.
Highlights: Prenatal ethanol exposures affect homeostatic responses after body sodium depletion. The 5HT – DRN system is chronically affected by prenatal ethanol exposure. The AVP hypothalamic neurons are chronically activated by prenatal ethanol exposure. Central extended Amygdala subnucleuses are chronically activated by prenatal ethanol exposure. Prenatal ethanol exposure increases the preference for alcohol during adolescence. Abstract: The aim of the present work is to analyze how prenatal binge-like ethanol exposure to a moderate dose (2.0 g/kg; group Pre-EtOH) during gestational days (GD) 17–20 affects hydroelectrolyte regulatory responses. This type of exposure has been observed to increase ethanol consumption during adolescence (postnatal day 30–32). In this study we analyzed basal brain neural activity and basal-induced sodium appetite (SA) and renal response stimulated by sodium depletion (SD) as well as voluntary ethanol consumption as a function of vehicle or ethanol during late pregnancy. In adolescent offspring, SD was induced by furosemide and a low-sodium diet treatment (FURO + LSD). Other animals were analyzed in terms of immunohistochemical detection of Fra-like (Fra-LI-ir) protein and serotonin (5HT) and/or vasopressin (AVP). The Pre-EtOH group exhibited heightened voluntary ethanol intake and a reduction in sodium and water intake induced by SD relative to controls. Basal Na and K concentrations in urine were also reduced in Pre-EtOH animals while the induced renal response after FURO treatment was similar across prenatal treatments. However, the correlation between urine volume and water intake induced by FURO significantly varied across these treatments. At the brain level of analysis, the number of basal Fra-LI-ir was significantly increased in AVP magnocellular neurons of the paraventricular nucleus (PVN) and in 5HT neurons in the dorsal raphe nucleus (DRN) in Pre-EtOH pups. In the experimental group, we also observed a significant increase in Fra-LI along the nucleus of the solitary tract (NTS) and in the central extended amygdala nuclei. In summary, moderate Pre-EtOH exposure produces long-lasting changes in brain organization, affecting basal activity of central extended amygdala nuclei, AVP neurons and the inhibitory areas of SA such as the NTS and the 5HT-DRN. These changes possibly modulate the above described variations in basal-induced drinking behaviors and renal regulatory responses.